A gas sensor and its preparation method and application
By modifying the zinc oxide/tungsten oxide film layer and interfinger electrode with platinum-containing substances in the gas-sensitive sensor, the problem of poor sensitivity to hydrogen detection at room temperature is solved, and hydrogen detection with high responsiveness and low detection limit is achieved , suitable for practical applications.
Patent Information
- Application Number
- CN202211309059.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-25
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2042-10-25
AI Technical Summary
The prior art is difficult to effectively detect hydrogen at room temperature, and zinc oxide has low selectivity to hydrogen, poor sensitivity, and difficult to achieve rapid response.
The gas-sensitive sensors that modify the zinc oxide/tungsten oxide thin film layer and the interdigit electrode are prepared by hydrothermal reaction and annealing treatment, using strong adsorption and desorption of platinum. Capacity and co-modification of tungsten oxide improves hydrogen response.
The hydrogen response is significantly improved at room temperature, with the detection limit as low as 1ppm, the response time is 14s and the reply time is 145s, which has good selectivity and stability, and is suitable for linear detection of different concentrations of hydrogen.
Smart Images

Figure CN115586235B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of gas detection, and in particular to a gas sensor and a preparation method and application thereof. Background Art
[0002] As a clean, efficient and sustainable energy source, hydrogen has been widely used in daily life and industrial production. However, since hydrogen is an odorless, tasteless and colorless highly flammable gas, its lower explosion limit (LEL) is 4.65% at room temperature. In addition, since hydrogen molecules are very small, they can leak through tiny cracks and holes at a high flow rate and do not take much time to reach explosive concentration levels. It can be seen that it is crucial to perform real-time detection and give early warning when a leak occurs to reduce potential hazards in practical applications. Therefore, it is crucial to develop a gas sensor with low detection limit, high sensitivity and fast response to hydrogen leaks in storage and transportation equipment.
[0003] As a typical n-type semiconductor with a band gap of 3.37 eV, zinc oxide has unique chemical adsorption and electronic properties in detecting oxidizing and reducing gases. In addition, zinc oxide has the characteristics of low cost, non-toxicity, fast electron migration, high ion binding energy and good physical and chemical stability. However, zinc oxide has low selectivity for specific gases (hydrogen), high detection temperature and poor sensitivity, making it difficult to effectively detect hydrogen at room temperature. Summary of the invention
[0004] The object of the present invention is to provide a gas sensor and a preparation method and application thereof. The gas sensor can effectively detect hydrogen at room temperature.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a gas sensor, comprising a substrate, a zinc oxide seed crystal layer, a zinc oxide / tungsten oxide thin film layer modified by a platinum-containing substance, and interdigital electrodes which are stacked in sequence;
[0007] The platinum-containing substance modified zinc oxide / tungsten oxide thin film layer is a zinc oxide thin film layer co-modified with tungsten oxide and the platinum-containing substance.
[0008] Preferably, the thickness of the zinc oxide seed layer is 40 to 100 nm;
[0009] The thickness of the zinc oxide / tungsten oxide thin film layer modified by the platinum-containing substance is 1.6 to 1.9 μm;
[0010] The thickness of the interdigital electrodes is 400-600 nm.
[0011] Preferably, the material of the interdigital electrodes is Pt, Au or Al.
[0012] The present invention also provides a method for preparing the gas sensor described in the above technical solution, comprising the following steps:
[0013] After coating the surface of the substrate with a zinc salt solution, a first annealing treatment is performed to obtain a substrate containing a zinc oxide seed crystal layer;
[0014] Mixing a soluble zinc salt, a base, hexachloroplatinic acid and water to obtain a mixed solution;
[0015] Placing the substrate containing the zinc oxide seed crystal layer in the mixed solution, performing a hydrothermal reaction, and then performing a second annealing treatment to prepare a zinc oxide film doped with a platinum-containing substance on the surface of the zinc oxide seed crystal layer;
[0016] After coating the surface of the zinc oxide film doped with the platinum-containing substance with a tungsten salt solution, a third annealing treatment is performed to obtain a zinc oxide / tungsten oxide film layer modified with the platinum-containing substance;
[0017] After sputtering interdigital electrodes on the surface of the zinc oxide / tungsten oxide thin film layer modified by the platinum-containing substance, a fourth annealing treatment is performed to obtain the gas sensor.
[0018] Preferably, the molar ratio of the tungsten salt to the soluble zinc salt in the tungsten salt solution is (6.5-40):100.
[0019] Preferably, the molar ratio of hexachloroplatinic acid to soluble zinc salt is (0.07-0.5):100.
[0020] Preferably, the temperature of the first annealing treatment is 500°C and the time is 30 minutes;
[0021] The temperature of the hydrothermal reaction is 90°C and the time is 4 to 8 hours;
[0022] The temperature of the second annealing treatment is 400° C. and the time is 20 minutes.
[0023] Preferably, the temperature of the third annealing treatment is 400-450°C and the time is 20 minutes;
[0024] The temperature of the fourth annealing treatment is 350° C., and the time is 10 to 20 minutes.
[0025] Preferably, the zinc salt solution is an ethanol solution of zinc acetate with a concentration of 0.0025 to 0.1 mol / L;
[0026] The concentration of the soluble zinc salt in the mixed solution is 0.03-0.07 mol / L, the concentration of the alkali is 0.03-0.07 mol / L, and the concentration of hexachloroplatinic acid is 1 g / 100 mL;
[0027] The tungsten salt solution is a 0.01-0.04 mol / L tungsten hexachloride ethanol solution.
[0028] The present invention also provides the use of the gas sensor described in the above technical solution or the gas sensor prepared by the preparation method described in the above technical solution in the field of hydrogen detection.
[0029] The present invention provides a gas sensor, comprising a substrate, a zinc oxide seed layer, a platinum-containing modified zinc oxide / tungsten oxide thin film layer and an interdigital electrode, which are stacked in sequence; the platinum-containing modified zinc oxide / tungsten oxide thin film layer is a zinc oxide thin film layer co-modified with tungsten oxide and a platinum-containing substance. In the present invention, the noble metal platinum has a higher work function, has a strong adsorption and desorption ability for hydrogen molecules, and the co-modification of the platinum-containing substance and the oxide provides more adsorption sites, reduces the activation energy required for hydrogen decomposition, and synergistically enhances the gas-sensitive response to hydrogen. According to the records of the embodiment, compared with pure zinc oxide, the zinc oxide film hydrogen sensor co-modified with tungsten oxide / platinum (platinum oxide) has a 24-fold increase in responsiveness to 100ppm of hydrogen at room temperature. And the response to 4000ppm hydrogen is as high as 3870, the response time is 14s, the response time is 145s, the detection limit is as low as 1ppm, and it has good selectivity and stability, and the response to H2 of different concentrations shows a good linear relationship, which is conducive to practical application.
[0030] The present invention also provides a method for preparing the gas sensor described in the above technical solution, comprising the following steps: coating the surface of the substrate with a zinc salt solution and then performing a first annealing treatment to obtain a substrate containing a zinc oxide seed crystal layer; mixing a soluble zinc salt, C6H 12 N4, hexachloroplatinic acid and water are mixed to obtain a mixed solution; the substrate containing the zinc oxide seed crystal layer is placed in the mixed solution, and after a hydrothermal reaction, a second annealing treatment is performed to prepare a zinc oxide film doped with a platinum-containing substance on the surface of the zinc oxide seed crystal layer; after a tungsten salt solution is coated on the surface of the zinc oxide film doped with the platinum-containing substance, a third annealing treatment is performed to obtain a zinc oxide / tungsten oxide film layer modified with a platinum-containing substance; after a cross-finger electrode is sputtered on the surface of the zinc oxide / tungsten oxide film layer modified with a platinum-containing substance, a fourth annealing treatment is performed to obtain the gas sensor. The preparation method has simple steps, low cost, strong operability, high repeatability, and low equipment requirements, and the gas sensor finally prepared has good repeatability and stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 XRD diagram (a) and partial enlarged diagram of (002) crystal plane and (103) crystal plane of the film with zinc oxide nanorod structure described in Comparative Example 1 and the zinc oxide film doped with platinum-containing substances described in Examples 1 to 4 (b);
[0032] Figure 2 SEM images of the zinc oxide nanorod structure film (a) described in Comparative Example 1, the ZnO (PtO / Pt 0.25%) prepared in Example 3 (b), and the zinc oxide / tungsten oxide film modified with platinum-containing material (c) prepared in Example 3;
[0033] Figure 3 This is a performance test diagram of the gas sensor described in Comparative Example 1 under different hydrogen concentrations;
[0034] Figure 4 This is a performance test diagram of the gas sensor described in Comparative Example 2 under different hydrogen concentrations;
[0035] Figure 5 This is a performance test diagram of the gas sensor described in Example 3 under different hydrogen concentrations;
[0036] Figure 6 This is a comparison chart of the sensing performance of the gas sensors described in Example 3 and Comparative Example 1 to hydrogen of different concentrations. DETAILED DESCRIPTION
[0037] The present invention provides a gas sensor, comprising a substrate, a zinc oxide seed crystal layer, a zinc oxide / tungsten oxide thin film layer modified by a platinum-containing substance, and interdigital electrodes which are stacked in sequence;
[0038] The platinum-containing substance modified zinc oxide / tungsten oxide thin film layer is a zinc oxide thin film layer co-modified with tungsten oxide and the platinum-containing substance.
[0039] The present invention has no special limitation on the type of the substrate, and any type familiar to those skilled in the art can be used. In an embodiment of the present invention, the substrate is specifically quartz glass with a size of 2.5 cm*2.5 cm*2 mm.
[0040] In the present invention, the thickness of the zinc oxide seed layer is preferably 40 to 100 nm, more preferably 50 to 80 nm, and most preferably 60 to 70 nm.
[0041] In the present invention, the thickness of the zinc oxide / tungsten oxide thin film layer modified by the platinum-containing substance is preferably 1.6 to 1.9 μm, more preferably 1.6 to 1.8 μm, and most preferably 1.6 to 1.7 μm. In the present invention, the platinum-containing substance preferably includes platinum and platinum oxide. In the present invention, the molar ratio of the Zn element to the W element in the zinc oxide / tungsten oxide thin film layer modified by the platinum-containing substance is preferably (1 to 6):100, more preferably (2 to 5):100, and most preferably (3 to 4):100.
[0042] In the present invention, the thickness of the interdigital electrodes is preferably 400-600 nm, more preferably 450-550 nm, and most preferably 480-520 nm. In the present invention, the material of the interdigital electrodes is preferably Pt, Au or Al, more preferably Pt or Au, and most preferably Pt.
[0043] The present invention also provides a method for preparing the gas sensor described in the above technical solution, comprising the following steps:
[0044] After coating the surface of the substrate with a zinc salt solution, a first annealing treatment is performed to obtain a substrate containing a zinc oxide seed crystal layer;
[0045] Mixing a soluble zinc salt, a base, hexachloroplatinic acid and water to obtain a mixed solution;
[0046] Placing the substrate containing the zinc oxide seed crystal layer in the mixed solution, performing a hydrothermal reaction, and then performing a second annealing treatment to prepare a zinc oxide film doped with a platinum-containing substance on the surface of the zinc oxide seed crystal layer;
[0047] After coating the surface of the zinc oxide film doped with the platinum-containing substance with a tungsten salt solution, a third annealing treatment is performed to obtain a zinc oxide / tungsten oxide film layer modified with the platinum-containing substance;
[0048] After sputtering interdigital electrodes on the surface of the zinc oxide / tungsten oxide thin film layer modified by the platinum-containing substance, a fourth annealing treatment is performed to obtain the gas sensor.
[0049] In the present invention, unless otherwise specified, all preparation raw materials are commercially available products well known to those skilled in the art.
[0050] The invention carries out a first annealing treatment after coating the surface of the substrate with a zinc salt solution to obtain a substrate containing a zinc oxide seed crystal layer.
[0051] In the present invention, the substrate is pretreated before the zinc salt solution is applied, and the pretreatment includes cleaning, drying and ultraviolet treatment in sequence; the cleaning preferably includes ultrasonic cleaning for 20 to 30 minutes each using acetone, anhydrous ethanol and deionized water in sequence; the present invention does not have any special restrictions on the frequency of the ultrasonic cleaning, and the process familiar to those skilled in the art can be used. The present invention does not have any special restrictions on the drying process, and the process familiar to those skilled in the art can be used. In the present invention, the ultraviolet treatment process preferably includes placing the substrate in a UV box, passing oxygen for 2 minutes, closing the air intake device, and maintaining it for 15 to 20 minutes.
[0052] In the present invention, the concentration of the zinc salt in the zinc salt solution is preferably 0.0025 to 0.1 mol / L, more preferably 0.0025 to 0.05 mol / L, and most preferably 0.0025 mol / L. In the present invention, the zinc salt preferably includes zinc acetate. In the present invention, the solvent in the zinc salt solution is preferably anhydrous ethanol.
[0053] In the present invention, the zinc salt solution is preferably prepared by mixing the zinc salt and a solvent. In the present invention, the mixing is preferably carried out under stirring. The present invention does not have any particular limitation on the stirring process, and the stirring process can be carried out using a process well known to those skilled in the art.
[0054] In the present invention, the coating method is preferably spin coating; the spin coating preferably includes a first spin coating and a second spin coating performed sequentially; the rotation speed of the first spin coating is preferably 1000 rpm; the time is preferably 10s; the rotation speed of the second spin coating is preferably 3000 rpm; the time is preferably 30s.
[0055] After the spin coating is completed, the present invention further preferably includes heating, and the heating temperature is preferably 125-150° C., more preferably 150° C.; the heating time is preferably 5-10 min, more preferably 5 min.
[0056] After the heating is completed, the present invention also preferably includes repeating the above spin coating and heating process 3 times.
[0057] In the present invention, the temperature of the first annealing treatment is preferably 500° C. and the time is preferably 30 minutes. The first annealing treatment is preferably performed in an air atmosphere.
[0058] The preparation method of the present invention further comprises mixing a soluble zinc salt, an alkali, hexachloroplatinic acid and water to obtain a mixed solution.
[0059] In the present invention, the soluble zinc salt is preferably zinc nitrate.
[0060] In the present invention, the base preferably comprises C6H 12 N4, sodium hydroxide or potassium hydroxide, more preferably C6H 12 N4. In the present invention, the base provides hydroxide ions to provide an alkaline environment for the subsequent growth of zinc oxide.
[0061] In the present invention, the hexachloroplatinic acid is preferably mixed in the form of a hexachloroplatinic acid aqueous solution, and the concentration of the hexachloroplatinic acid aqueous solution is preferably 1 g / 100 mL.
[0062] In the present invention, the concentration of the soluble zinc salt in the mixed solution is preferably 0.03 to 0.07 mol / L, and the concentration of the alkali is preferably 0.03 to 0.07 mol / L.
[0063] In the present invention, the molar ratio of hexachloroplatinic acid to soluble zinc salt is preferably (0.07-5):100, more preferably (0.1-0.4):100, and most preferably (0.2-0.3):100.
[0064] In the present invention, the mixing is preferably carried out under stirring conditions. The present invention does not have any special limitation on the stirring process, and the stirring process may be carried out using a process well known to those skilled in the art.
[0065] After obtaining the substrate containing the zinc oxide seed crystal layer and the mixed solution, the present invention places the substrate containing the zinc oxide seed crystal layer in the mixed solution, performs a hydrothermal reaction, and then performs a second annealing treatment to prepare a zinc oxide film doped with platinum on the surface of the zinc oxide seed crystal layer.
[0066] In the present invention, the temperature of the hydrothermal reaction is preferably 90° C.; the time is preferably 4 to 8 hours, more preferably 8 hours.
[0067] After the hydrothermal reaction is completed, the present invention also preferably includes cooling, washing, soaking and drying in sequence. The cooling is preferably natural cooling; the washing is preferably washing with deionized water; the soaking is preferably soaking in deionized water for 3 hours; the drying temperature is preferably 60°C.
[0068] In the present invention, the second annealing treatment is preferably performed in an air atmosphere, the temperature of the second annealing treatment is preferably 400° C., and the time is preferably 20 minutes.
[0069] After a zinc oxide film doped with platinum is prepared on the surface of the zinc oxide seed crystal layer, the present invention applies a tungsten salt solution on the surface of the zinc oxide film doped with platinum and then performs a third annealing treatment to obtain a zinc oxide / tungsten oxide film layer modified with platinum.
[0070] In the present invention, the tungsten salt solution is preferably a 0.01-0.04 mol / L tungsten hexachloride ethanol solution, and more preferably a 0.04 mol / L tungsten hexachloride ethanol solution.
[0071] In the present invention, the molar ratio of the tungsten salt to the soluble zinc salt in the tungsten salt solution is preferably (6.5-40):100, more preferably (13-33):100, and most preferably (19.5-26):100.
[0072] In the present invention, the method for preparing the tungsten salt solution preferably comprises mixing a tungsten salt and a solvent to obtain the tungsten salt solution. In the present invention, the mixing is preferably carried out under ultrasonic conditions. The present invention has no special limitation on the ultrasonic process, and the process well known to those skilled in the art can be used.
[0073] In the present invention, the coating method is preferably spin coating; the spin coating preferably includes a first spin coating and a second spin coating performed sequentially; the rotation speed of the first spin coating is preferably 1000 rpm; the time is preferably 10s; the rotation speed of the second spin coating is preferably 3000 rpm; the time is preferably 20s.
[0074] After the spin coating is completed, the present invention further preferably includes heating, and the heating temperature is preferably 100-125° C., more preferably 100° C.; the heating time is preferably 5-10 min, more preferably 5 min.
[0075] After the heating is completed, the present invention also preferably includes repeating the above spin coating and heating process 3 times.
[0076] In the present invention, the temperature of the third annealing treatment is preferably 400-450° C., more preferably 400° C., and the time is preferably 20 minutes. The third annealing treatment is preferably performed in an air atmosphere.
[0077] After obtaining the zinc oxide / tungsten oxide thin film layer modified with the platinum-containing substance, the present invention performs a fourth annealing treatment after sputtering interdigital electrodes on the surface of the zinc oxide / tungsten oxide thin film layer modified with the platinum-containing substance to obtain the gas sensor.
[0078] In the present invention, the interdigital electrode is preferably a Pt interdigital electrode, and the preparation method of the Pt interdigital electrode preferably comprises: installing a Pt target with a purity of 99.99% on a cathode target of a magnetron sputtering system, covering a cross-shaped mask on the surface of the zinc oxide / tungsten oxide film modified with a platinum-containing substance, and using this as a substrate, adjusting the distance between the cathode target and the substrate to 60 mm, and evacuating to 10 -4 After the pressure drops below Pa, argon gas is introduced at a flow rate of 14.4 sccm and the working gas pressure is maintained at 0.5 Pa for DC sputtering. The power of the DC sputtering is 40 W and the time is 5 min to prepare a metal Pt interdigital electrode.
[0079] In the present invention, the temperature of the fourth annealing treatment is preferably 350° C., the time is preferably 10 to 20 minutes, more preferably 20 minutes, and the fourth annealing treatment is preferably performed in an air atmosphere.
[0080] The present invention also provides the use of the gas sensor described in the above technical solution or the gas sensor prepared by the preparation method described in the above technical solution in detecting hydrogen. The present invention has no special limitation on the method of the application, and the method well known to those skilled in the art can be used.
[0081] The gas sensor provided by the present invention and its preparation method and application are described in detail below in conjunction with the embodiments, but they should not be understood as limiting the protection scope of the present invention.
[0082] Example 1
[0083] A quartz glass substrate of 2.5 cm*2.5 cm*2 mm was used as the substrate, and ultrasonic cleaning was performed with acetone, anhydrous ethanol and deionized water for 20 minutes in sequence. After drying, it was placed in a UV box, oxygen was passed for 2 minutes, and then the air inlet device was closed and maintained for 15 minutes to obtain a pretreated quartz glass substrate.
[0084] Mix 10.98 mg Zn(CH3COO)2·2H2O with 20 mL anhydrous ethanol and stir until completely dissolved to obtain a zinc oxide seed layer precursor solution;
[0085] A pipette gun is used to drop 125 μL of the zinc oxide seed crystal layer precursor on the surface of the pretreated quartz glass substrate, and a spin coater is used for spin coating, wherein the spin coating includes a first step of spin coating and a second step of spin coating; the first step of spin coating has a rotation speed of 1000 rpm and a time of 10 s, and the second step of spin coating has a rotation speed of 3000 rpm and a time of 30 s. After the spin coating is completed, the substrate is placed on a heating table and heated at 150° C. for 5 min. After repeating the above spin coating and heating process 3 times, a first annealing treatment is performed in an air atmosphere (the temperature of the first annealing treatment is 500° C. and the time is 30 min), to obtain a substrate containing a zinc oxide seed crystal layer (the thickness of the zinc oxide seed crystal layer is 60 to 70 nm);
[0086] 0.8923g Zn(NO3)2 and 0.4205g C6H 12 N4, 77 μL H2PtCl6·6H2O with a concentration of 1 g / 100 ML and 60 mL deionized water were stirred until fully dissolved to obtain a mixed solution;
[0087] After placing the substrate containing the zinc oxide seed layer in the mixed solution, performing a hydrothermal reaction at 90° C. in a hydrothermal reactor for 8 hours, the film is naturally cooled to room temperature, and the film is taken out, washed with deionized water, immersed in deionized water for 3 hours, dried at 60° C. for 120 minutes, and then subjected to a second annealing treatment in an air atmosphere (the temperature of the second annealing treatment is 400° C. and the time is 20 minutes) to obtain a zinc oxide film doped with a platinum-containing substance (the platinum-containing substance includes a single substance of platinum and platinum oxide; recorded as ZnO (PtO / Pt0.07%));
[0088] Dissolve 317.2 mg WCl6 and 20 mL anhydrous ethanol under ultrasonic conditions to obtain a tungsten oxide precursor solution;
[0089] A 125 μL drop of the tungsten oxide precursor is spin-coated on the surface of the zinc oxide film doped with the platinum-containing substance by using a pipette gun, and the spin coating includes a first step of spin coating and a second step of spin coating; the first step of spin coating has a rotation speed of 1000 rpm and a time of 10 s, and the second step of spin coating has a rotation speed of 3000 rpm and a time of 20 s. After the spin coating is completed, it is placed on a heating table and heated at 100° C. for 5 min. After repeating the above spin coating and heating process 3 times, a third annealing treatment is performed (the temperature of the third annealing treatment is 400° C., the time is 20 min, and the atmosphere is air), and a tungsten oxide film is generated on the surface of the zinc oxide film doped with the platinum-containing substance (recorded as a platinum-containing substance modified zinc oxide / tungsten oxide film);
[0090] A Pt target with a purity of 99.99% was installed on the cathode target of the magnetron sputtering system. A cross-shaped mask was placed on the surface of the zinc oxide / tungsten oxide film modified with platinum-containing substances and used as a substrate. The distance between the cathode target and the substrate was adjusted to 60 mm, and the vacuum was pumped to 10 -4 After the pressure drops below Pa, argon gas is introduced at a flow rate of 14.4 sccm and the working gas pressure is maintained at 0.5 Pa for DC sputtering. The power of the DC sputtering is 40 W and the time is 5 min. After the metal Pt interdigital electrode is prepared, the fourth annealing treatment is carried out (the temperature of the fourth annealing treatment is 350°C, the time is 20 min, and the atmosphere is air) to obtain a gas sensitive sensor.
[0091] Example 2
[0092] Refer to Example 1, the difference is that the 77 μL H2PtCl6·6H2O with a concentration of 1g / 100ML is replaced by 155 μL H2PtCl6·6H2O with a concentration of 1g / 100ML, and the obtained zinc oxide film doped with platinum-containing substances (the platinum-containing substances include platinum element and platinum oxide; recorded as ZnO (PtO / Pt 0.125%)).
[0093] Example 3
[0094] Referring to Example 1, the difference is that the 77 μL H2PtCl6·6H2O with a concentration of 1 g / 100ML is replaced by 315 μL H2PtCl6·6H2O with a concentration of 1 g / 100ML, and the obtained zinc oxide film doped with a platinum-containing substance (the platinum-containing substance includes platinum element and platinum oxide; the molar ratio of the platinum element and platinum oxide is 2:1, recorded as ZnO (PtO / Pt 0.25%));
[0095] The obtained gas sensor was tested at different hydrogen concentrations at room temperature. The test results are as follows: Figure 5 As shown by Figure 5 It can be seen that the detectable range of the gas sensor is 1-4000 ppm, the detection limit is as low as 1 ppm, the response value is 13.29, the response time is 71 s, and the recovery time is 31 s.
[0096] Example 4
[0097] Refer to Example 1, the difference is that the 77 μL H2PtCl6·6H2O with a concentration of 1g / 100ML is replaced by 630 μL H2PtCl6·6H2O with a concentration of 1g / 100ML, and the obtained zinc oxide film doped with platinum-containing substance (the platinum-containing substance includes platinum element and platinum oxide, recorded as ZnO (PtO / Pt 0.5%)).
[0098] Comparative Example 1
[0099] A quartz glass substrate of 2.5 cm*2.5 cm*2 mm was used as the substrate, and ultrasonic cleaning was performed with acetone, anhydrous ethanol and deionized water for 20 minutes in sequence. After drying, it was placed in a UV box, oxygen was passed for 2 minutes, and then the air inlet device was closed and maintained for 15 minutes to obtain a pretreated quartz glass substrate.
[0100] Mix 10.98 mg Zn(CH3COO)2·2H2O with 20 mL anhydrous ethanol and stir until completely dissolved to obtain a zinc oxide seed layer precursor solution;
[0101] A pipette gun is used to drop 125 μL of the zinc oxide seed crystal layer precursor on the surface of the pretreated quartz glass substrate, and a spin coater is used for spin coating, wherein the spin coating includes a first step of spin coating and a second step of spin coating; the first step of spin coating has a rotation speed of 1000 rpm and a time of 10 s, and the second step of spin coating has a rotation speed of 3000 rpm and a time of 30 s. After the spin coating is completed, the substrate is placed on a heating table and heated at 150° C. for 5 min. After repeating the above spin coating and heating process 3 times, a first annealing treatment is performed in an air atmosphere (the temperature of the first annealing treatment is 500° C. and the time is 30 min), to obtain a substrate containing a zinc oxide seed crystal layer (the thickness of the zinc oxide seed crystal layer is 60 to 70 nm);
[0102] 0.8923g Zn(NO3)2 and 0.4205g C6H 12 N4 and 60 mL of deionized water were stirred until fully dissolved to obtain a mixed solution;
[0103] After placing the substrate containing the zinc oxide seed crystal layer in the mixed solution, performing a hydrothermal reaction at 90° C. in a hydrothermal reactor for 8 hours, naturally cooling to room temperature, taking out the film, washing the film with deionized water, soaking it in deionized water for 3 hours, drying it at 60° C., and performing a second annealing treatment in an air atmosphere (the temperature of the second annealing treatment is 400° C., and the time is 20 minutes), to obtain a film having a zinc oxide nanorod structure;
[0104] A Pt target with a purity of 99.99% was installed on the cathode target of the magnetron sputtering system, a cross-shaped mask was placed on the surface of the film with the zinc oxide nanorod structure, and this was used as the substrate. The distance between the cathode target and the substrate was adjusted to 60 mm, and the vacuum was evacuated to 10 -4 Pa or less, argon gas was introduced at a flow rate of 14.4 sccm, and the working gas pressure was maintained at 0.5 Pa, and DC sputtering was performed, the power of the DC sputtering was 40 W, and the time was 5 min. After the metal Pt interdigital electrode was prepared, a third annealing treatment was performed (the temperature of the third annealing treatment was 350 ° C, the time was 10 min, and the atmosphere was air) to obtain a gas sensor;
[0105] The gas sensor was tested at different hydrogen concentrations at room temperature. The test results are as follows: Figure 3 As shown by Figure 3 It can be seen that the gas sensor has a low response to hydrogen, and the response time and recovery time are too long;
[0106] Figure 1 The XRD diagram (a) and the partial enlarged diagram (b) of the (002) crystal plane and (103) crystal plane of the zinc oxide thin film with a zinc oxide nanorod structure described in Comparative Example 1 and the zinc oxide thin film doped with a platinum-containing substance described in Examples 1 to 4 are shown in FIG. Figure 1 (a) It can be seen that the film with zinc oxide nanorod structure and the zinc oxide film doped with platinum-containing substances described in Example 3 are both oriented on the (002) crystal plane. Figure 1 (b) It can be seen that as the amount of platinum-containing material doping increases, the zinc oxide undergoes lattice expansion;
[0107] Figure 2 The SEM images of the zinc oxide nanorod structure film (a) of Comparative Example 1, the ZnO (PtO / Pt 0.25%) prepared in Example 3 (b) and the zinc oxide / tungsten oxide film modified with platinum-containing substances prepared in Example 3 (c) are shown in FIG. Figure 2(a) It can be seen that the average diameter of the zinc oxide nanorods in the film having the zinc oxide nanorod structure is about 115 nm, and the nanorods are dispersed; Figure 2 (b) It can be seen that compared with the comparative example, the morphology of zinc oxide doped with platinum-containing substances changes, and the structure is more compact; Figure 2 (c) It can be seen that the surface of the ZnO (PtO / Pt 0.25%) is corroded by the tungsten hexachloride ethanol solution and tungsten oxide is attached;
[0108] Figure 6 This is a comparison chart of the sensing performance of the gas sensor of Example 3 and Comparative Example 1 for different concentrations of hydrogen. Figure 6 It can be seen that the gas sensor described in Example 3 has a 24-fold increase in responsiveness to 100 ppm of hydrogen at room temperature, a detection range of 1 to 4000 ppm, and a response to 4000 ppm of hydrogen as high as 3870, a response time of 14 s, a recovery time of 145 s, a detection limit as low as 1 ppm, a response value of 13.29, and has a good linear relationship.
[0109] Comparative Example 2
[0110] A quartz glass substrate of 2.5 cm*2.5 cm*2 mm was used as the substrate, and ultrasonic cleaning was performed with acetone, anhydrous ethanol and deionized water for 20 minutes in sequence. After drying, it was placed in a UV box, oxygen was passed for 2 minutes, and then the air inlet device was closed and maintained for 15 minutes to obtain a pretreated quartz glass substrate.
[0111] Mix 10.98 mg Zn(CH3COO)2·2H2O with 20 mL anhydrous ethanol and stir until completely dissolved to obtain a zinc oxide seed layer precursor solution;
[0112] A pipette gun is used to drop 125 μL of the zinc oxide seed crystal layer precursor on the surface of the pretreated quartz glass substrate, and a spin coater is used for spin coating, wherein the spin coating includes a first step of spin coating and a second step of spin coating; the first step of spin coating has a rotation speed of 1000 rpm and a time of 10 s, and the second step of spin coating has a rotation speed of 3000 rpm and a time of 30 s. After the spin coating is completed, the substrate is placed on a heating table and heated at 150° C. for 5 min. After repeating the above spin coating and heating process 3 times, a first annealing treatment is performed in an air atmosphere (the temperature of the first annealing treatment is 500° C. and the time is 30 min), to obtain a substrate containing a zinc oxide seed crystal layer (the thickness of the zinc oxide seed crystal layer is 60 to 70 nm);
[0113] 0.8923g Zn(NO3)2 and 0.4205g C6H 12N4 and 60 mL of deionized water were stirred until fully dissolved, and then 315 μL of H2PtCl6·6H2O solution with a concentration of 1 g / 100 mL was pipetted dropwise with a pipette and added under stirring to obtain a mixed solution;
[0114] After placing the substrate containing the zinc oxide seed layer in the mixed solution, performing a hydrothermal reaction at 90° C. in a hydrothermal reactor for 8 hours, naturally cooling to room temperature, taking out the film, washing the film with deionized water, soaking it in deionized water for 3 hours, drying it at 60° C., and performing a second annealing treatment in an air atmosphere (the temperature of the second annealing treatment is 400° C., and the time is 20 minutes), to obtain a zinc oxide film modified with a platinum-containing substance;
[0115] A Pt target with a purity of 99.99% was installed on the cathode target of the magnetron sputtering system. A cross-shaped mask was placed on the surface of the zinc oxide film modified with the platinum-containing substance and used as the substrate. The distance between the cathode target and the substrate was adjusted to 60 mm, and the vacuum was evacuated to 10 -4 Pa or less, argon gas was introduced at a flow rate of 14.4 sccm, and the working gas pressure was maintained at 0.5 Pa, and DC sputtering was performed, the power of the DC sputtering was 40 W, and the time was 5 min. After the metal Pt interdigital electrode was prepared, a third annealing treatment was performed (the temperature of the third annealing treatment was 350 ° C, the time was 20 min, and the atmosphere was air) to obtain a gas sensor;
[0116] The gas sensor was tested at different hydrogen concentrations at room temperature. The test results are as follows: Figure 4 As shown by Figure 4 It can be seen that the gas sensor has poor selectivity for hydrogen and lacks response regularity.
[0117] Test Case
[0118] The gas sensors described in Examples 1 to 4 and Comparative Example 1 were tested for responsiveness to hydrogen (concentration of 100 ppm) at room temperature. The test results are shown in Table 1:
[0119] Table 1 Test results of the gas sensors described in Examples 1 to 4 and Comparative Example 1
[0120] Response (Ra / Rg) Response time(s) Response time(s) Comparative Example 1 2.67 211 308 Comparative Example 2 -- -- -- Example 1 27.02 34 128 Example 2 46.04 98 181 Example 3 61.5 19 81 Example 4 16.81 22 191
[0121] Note: “--” means no response
[0122] It can be seen from Table 1 that the gas sensor of the present invention has high selectivity and responsiveness to hydrogen at room temperature.
[0123] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A gas sensor, characterized in that: It includes a substrate, a zinc oxide seed crystal layer, a zinc oxide / tungsten oxide thin film layer modified by a platinum-containing substance, and an interdigital electrode which are stacked in sequence; The zinc oxide / tungsten oxide thin film layer modified by the platinum-containing substance is a zinc oxide thin film layer co-modified by tungsten oxide and the platinum-containing substance; The method for preparing the gas sensor comprises the following steps: After coating the surface of the substrate with a zinc salt solution, a first annealing treatment is performed to obtain a substrate containing a zinc oxide seed crystal layer; Mixing a soluble zinc salt, a base, hexachloroplatinic acid and water to obtain a mixed solution; Placing the substrate containing the zinc oxide seed crystal layer in the mixed solution, performing a hydrothermal reaction, and then performing a second annealing treatment to prepare a zinc oxide film doped with a platinum-containing substance on the surface of the zinc oxide seed crystal layer; After coating the surface of the zinc oxide film doped with the platinum-containing substance with a tungsten salt solution, a third annealing treatment is performed to obtain a zinc oxide / tungsten oxide film layer modified with the platinum-containing substance; After sputtering interdigital electrodes on the surface of the zinc oxide / tungsten oxide thin film layer modified by the platinum-containing substance, a fourth annealing treatment is performed to obtain the gas sensor.
2. The gas sensor according to claim 1, characterized in that: The thickness of the zinc oxide seed crystal layer is 40 to 100 nm; The thickness of the zinc oxide / tungsten oxide thin film layer modified by the platinum-containing substance is 1.6 to 1.9 μm; The thickness of the interdigital electrodes is 400-600 nm.
3. The gas sensor according to claim 1 or 2, characterized in that: The material of the interdigital electrodes is Pt, Au or Al.
4. The method for preparing the gas sensor according to any one of claims 1 to 3, characterized in that: The following steps are involved: After coating the surface of the substrate with a zinc salt solution, a first annealing treatment is performed to obtain a substrate containing a zinc oxide seed crystal layer; Mixing a soluble zinc salt, a base, hexachloroplatinic acid and water to obtain a mixed solution; Placing the substrate containing the zinc oxide seed crystal layer in the mixed solution, performing a hydrothermal reaction, and then performing a second annealing treatment to prepare a zinc oxide film doped with a platinum-containing substance on the surface of the zinc oxide seed crystal layer; After coating the surface of the zinc oxide film doped with the platinum-containing substance with a tungsten salt solution, a third annealing treatment is performed to obtain a zinc oxide / tungsten oxide film layer modified with the platinum-containing substance; After sputtering interdigital electrodes on the surface of the zinc oxide / tungsten oxide thin film layer modified by the platinum-containing substance, a fourth annealing treatment is performed to obtain the gas sensor.
5. The preparation method according to claim 4, characterized in that: The molar ratio of the tungsten salt to the soluble zinc salt in the tungsten salt solution is (6.5-40):
100.
6. The preparation method according to claim 4, characterized in that: The molar ratio of the hexachloroplatinic acid to the soluble zinc salt is (0.07-0.5):
100.
7. The preparation method according to claim 4, characterized in that: The temperature of the first annealing treatment is 500°C and the time is 30 minutes; The temperature of the hydrothermal reaction is 90°C and the time is 4 to 8 hours; The temperature of the second annealing treatment is 400° C. and the time is 20 minutes.
8. The preparation method according to claim 4, characterized in that: The third annealing treatment is performed at a temperature of 400-450°C and a time of 20 minutes; The temperature of the fourth annealing treatment is 350° C., and the time is 10 to 20 minutes.
9. The preparation method according to claim 4, characterized in that: The zinc salt solution is an ethanol solution of zinc acetate with a concentration of 0.0025 to 0.1 mol / L; The concentration of the soluble zinc salt in the mixed solution is 0.03-0.07 mol / L, the concentration of the alkali is 0.03-0.07 mol / L, and the concentration of hexachloroplatinic acid is 1 g / 100 mL; The tungsten salt solution is a 0.01-0.04 mol / L tungsten hexachloride ethanol solution.
10. Use of the gas sensor according to any one of claims 1 to 3 or the gas sensor prepared by the preparation method according to any one of claims 4 to 9 in detecting hydrogen.